Life After Rehab: Experiences of Discharged Youth Offenders with Crime Desistance - Docena, Pierce S. (Silliman Journal, 2022)
This study explored the experiences of former youth offenders regarding crime desistance. Guided by the life story method in research, the researcher interviewed ten male youth offenders who had been discharged from the Regional Rehabilitation Center for Youth (RRCY) in Eastern Visayas. The narratives of the research participants revealed that desistance from crime is a long and difficult process influenced by various factors such as family support, condition of one’s community, intervention of significant persons, having a job, getting married, and having children. Implications for crime desistance studies are discussed and the challenges and opportunities for researchers and professionals who deal with youth offenders are likewise examined.